Perancangan Sistem Informasi Pengadaan Barang Berbasis Web pada PT XYZ Kota Depok - Muhammad Rizky Perdana; Muhammad Raulfie Al Adzani; Yohanes Beharato Lase; Anak Agung Gede Adwitya Yudaya Aryuntra (Jurnal Teknik Informatika dan Teknologi Informasi, 2025)
The procurement process is a critical activity that supports the operational continuity of a company. However, manual procurement procedures often lead to issues such as delayed documentation, data duplication, inaccurate information, and difficulty in tracking records. This study aims to design a web-based procurement information system for PT XYZ in Depok City to ensure that procurement activities are managed in an integrated, efficient, and accurate manner. The development method used in this research is the Prototype model, which allows direct interaction between developers and users, enabling iterative validation of system requirements. Data were collected through observation, interviews, and literature review to obtain a comprehensive understanding of user needs. The system design includes process modeling using UML diagrams, database modeling with ERD and LRS, and the creation of a system interface prototype. Based on black-box testing, essential functions such as user authentication performed as expected. The resulting system design is considered capable of improving data recording effectiveness, accelerating ordering processes, and simplifying procurement monitoring. This research serves as a foundation for future system development and full implementation within the company.